2001
DOI: 10.1002/j.2048-7940.2001.tb01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Nursing in Home Care

Abstract: A randomized sample of 83 members of the Association of Rehabilitation Nurses' (ARN's) Home Health Special Interest Group (SIG) responded to a survey in 1998 and 1999 to determine the role intensity of rehabilitation nurses in home care. An instrument was developed that was based on role descriptions formulated by ARN. Significant differences in the roles were reported for caregiver, case manager, counselor, family-client educator, advocate, administrator, student/staff educator, and researcher. Rewards of hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…(1) bed capacity of the nursing/convalescent homes and (2) increasing rehabilitation capacity (number of municipality-based ambulatory teams). The ideals of the Coordination Reform are consistent with studies which demonstrated the benefit of interdisciplinary at-home rehabilitation treatment of the elderly and patients with chronic illnesses (Wilson et al 1999;Hayward 2005;Vass et al 2007;Brillhart, Heard, and Kruse 2001;McColl et al 2009;Ranheim et al 2010), as opposed to multidisciplinary in-patient rehabilitation whose efficacy has been questioned (Ollonqvist et al 2007(Ollonqvist et al , 2008Johansson, Eklund, and Gosman-Hedstrom 2010). Prioritizing rehabilitation may lessen the bottlenecks experienced at the level of the municipal health care services (Tingvoll and Saeterstrand 2008).…”
Section: Discussionsupporting
confidence: 59%
“…(1) bed capacity of the nursing/convalescent homes and (2) increasing rehabilitation capacity (number of municipality-based ambulatory teams). The ideals of the Coordination Reform are consistent with studies which demonstrated the benefit of interdisciplinary at-home rehabilitation treatment of the elderly and patients with chronic illnesses (Wilson et al 1999;Hayward 2005;Vass et al 2007;Brillhart, Heard, and Kruse 2001;McColl et al 2009;Ranheim et al 2010), as opposed to multidisciplinary in-patient rehabilitation whose efficacy has been questioned (Ollonqvist et al 2007(Ollonqvist et al , 2008Johansson, Eklund, and Gosman-Hedstrom 2010). Prioritizing rehabilitation may lessen the bottlenecks experienced at the level of the municipal health care services (Tingvoll and Saeterstrand 2008).…”
Section: Discussionsupporting
confidence: 59%
“…Unrestrained household pets may also present as a safety threat for HC staff (Fitzwater & Gates , Sylvester & Reisener , Brillhart et al . , Gershon et al . , Henriksen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, HC workers report feeling unsafe in dangerous neighbourhoods (Brillhart et al . , Gershon et al . , Henriksen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If home health care workers do not feel safe, they will limit the amount of time spent completing the patient assessment, education, and visit(s) or lessen the frequency of visits, which may have a negative impact on patient outcomes (Brillhart, Kruse, & Heard, 2004;Campbell et al, 2013;Campbell et al, 2015;Kendra, Weiker, Simon, Grant, & Shullick, 1996). A study by Kendra and colleagues (1996) found that 68% of homecare workers would cut short a visit with a consumer if they felt unsafe in the home (Kendra et al, 1996).…”
Section: Safety Concerns Involving Hud-vash Recipientsmentioning
confidence: 99%